A new series of lanthanide-based complexes with a bis(hydroxy)benzoxaborolone ligand: synthesis, crystal structure, and magnetic and optical properties. Issue 11 (20th February 2020) - Abdallah, Ahmad; Puget, Marin; Daiguebonne, Carole; Suffren, Yan; Calvez, Guillaume; Bernot, Kevin; Guillou, Olivier
Abstract : Reactions, under hydrothermal conditions, between lanthanide chlorides and the sodium salt of 2-carboxyphenylboronic acid lead to a series of lanthanide-based complexes with general chemical formula [Ln2 (C7 H5 O2 )4 (C7 O4 H6 B)2 ·4H2 O] with Ln = Eu–Dy. Abstract : Reactions, under hydrothermal conditions, between lanthanide chlorides and the sodium salt of 2-carboxyphenylboronic acid lead to a series of lanthanide-based complexes with general chemical formula [Ln2 (C7 H5 O2 )4 (C7 O4 H6 B)2 ·4H2 O] with Ln = Eu–Dy. During the synthetic process, the 2-carboxyphenylboronate ligand decomposes leading to benzoate (C7 H5 O2 ) and bis(hydroxy)benzoxaborolone (C7 O2 H6 B). The crystal structure was solved on the basis of the Tb-derivative. It crystalizes in the triclinic system, space group P 1̄ (n° 2) with a = 9.3329(13) Å, b = 16.012(2) Å, c = 16.212(2) Å, α = 107.789(5)°, β = 90.226(5)°, γ = 97.585(5)°, V = 2284.16(52) Å 3 and Z = 2. Its crystal structure can be described on the basis of di-lanthanides entities surrounded by ligands. Compounds that constitute this series are thermally stable up to 190 °C. Solid-state luminescence properties have been studied in detail. The magnetic properties of the Dy-derivative have also been explored. It exhibits single molecule magnet behavior. Single crystals of the sodium salt of 2-carboxyphenylboronic acid with chemical formula [Na(C7 O4 H6 B)(H2 O)]∞ have also been obtained during this study. This compound crystallizes in the orthorhombic system, space group P 21 21 21 (n° 19) with a = 4.5881(13) Å, b = 6.5905(16) Å, c = 29.644(8) Å, V = 897.0(4) Å 3 and Z = 4. Its crystal structure is 2D and can be described as zigzag chains of sodium 2-carboxyphenylboronate bound to each other by coordination water molecules.